The transition of palliative care from the hospital to the home: a narrative review of experiences of patients and family caretakers - Arias Rojas, Mauricio; García-Vivar, Cristina (Investigación y Educación en Enfermería, 2015)
Objective. This work sought to identify, analyze, and synthesize the qualitative studies published on the experiences of patients and family caretakers during the transition of palliative care from the hospital to the home. Methodology. A narrative review was conducted on the PubMed, Cochrane Central, ScienceDirect, Ovid Nursing, CINALH, Scielo, and Bireme databases, from 2000 to 2014. Results. After the analysis and comparison of the data, the results were grouped into six themes: (1) the dyad and its knowledge regarding the diagnosis and prognosis; (2) emotions experienced by the family caretaker and the patient during discharge; (3) effective communication among those involved with the care; (4) education for the care of the person at home; (5) continuous support to the dyad at home, and (6) care overload: social support for the family caretaker. Conclusion. Patients and relatives in palliative care experience a broad range of needs during the transition process from the hospital to the home, which are often not covered by healthcare professionals. This review evidences the need to research further on the experiences of these families, especially during the stage prior to the transfer to the domicile. How to cite this article: Arias M, García-Vivar C. The transition of palliative care from the hospital to the home: a narrative review of experiences of patients and family caretakers. Invest Educ Enferm. 2015; 33(3):